Using E-learning in Teaching the Quality of the Practical Oral Pathology on Dentistry Students - Sepideh Vosough Hosseini; Amirala Aghbali; Parya Emamverdizadeh; Aila Hasani; Mohammad Razbani (Tabriz University of Medical Sciences, 2014)
Introduction: The rapid development in computer technology and the wide availability of personal computers together with the Internet, email, and various medical literature retrieval applications have changed both the study and the practice environments in dentistry, as they have in other fields. Electronic learning allows students to work at their own time and pace. In the field of pathology, this is even more important because by traditional methods, the review of lessons is only possible in labs and with presence of microscopes. This study aimed at evaluating the efficacy of a new educational technique in the field of practical pathology in dentistry.Methods: In this quasi experimental, combined with retrospective and prospective study, 82 dentistry students were recruited from Tabriz Faculty of Dentistry. The final scores of the 41 students whose course was based on a traditional method (Traditional Group) in the field of practical pathology were recorded. In the other group, however, a software containing multimedia information with the slides related to pathologic samples was provided along with the traditional educational method and the scores were recorded (New Group). Results: The mean score of practical pathology was 16.23±3.36 (range 8-20) in the new group and it was 15.22±3.52 (range 5-20) in the traditional group. Accordingly, the mean scores of the students in the new group were higher than the traditional group; however, this difference was not statistically significant (P=0.19). Conclusions: The scores of the practical pathology in dentistry may be enhanced if the traditional method is conducted along with supplementary multimedia software.